2007
DOI: 10.1128/jvi.02309-06
|View full text |Cite
|
Sign up to set email alerts
|

Rhinovirus Activates Interleukin-8 Expression via a Src/p110β Phosphatidylinositol 3-Kinase/Akt Pathway in Human Airway Epithelial Cells

Abstract: Rhinovirus (RV) is a single-stranded RNA virus from the Picornaviridae family responsible for the majority of common colds. Viral infections trigger the majority of asthma exacerbations (17, 22), and RV accounts for 60% of virus-induced exacerbations (17). RV is also an important trigger of chronic obstructive pulmonary disease exacerbations (28,32).Numerous studies suggest a role for interleukin-8 (IL-8) in the pathogenesis of asthma and chronic obstructive pulmonary disease (COPD) exacerbations. IL-8, a CXC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 39 publications
3
37
0
Order By: Relevance
“…Previous studies have shown that RV-39 (a major group virus)-induced IL-8 expression in epithelial cells occurred by ICAM binding and activation of PI3K (17,22). In our studies, we also found that inhibition of PI3K down-regulated both IL-8 and IL-6 mRNA induced by RV1b.…”
Section: Discussionsupporting
confidence: 75%
“…Previous studies have shown that RV-39 (a major group virus)-induced IL-8 expression in epithelial cells occurred by ICAM binding and activation of PI3K (17,22). In our studies, we also found that inhibition of PI3K down-regulated both IL-8 and IL-6 mRNA induced by RV1b.…”
Section: Discussionsupporting
confidence: 75%
“…Similar observations have been made in dendritic cells where Syk deficiency in dendritic cells derived from Syk knockout mice (29) or dendritic cells treated with pharmacological inhibitors (66) exhibited impaired Fc␥R-mediated internalization and presentation of MHC class II-restricted Ags. Syk-mediated endosomal traffic regulates other aspects of (14,44). Open arrows denote the HRV-induced signaling pathway described in the current article identifying Syk to be downstream of Src and to mediate PI3K activation and clathrin-mediated endocytosis of HRV.…”
Section: Discussionmentioning
confidence: 91%
“…TNF-a disrupts airway epithelial barrier function and this is mediated via Src activation and prevented by a Src inhibitor SU6656 [2,3-dihydro-N,N-dimethyl-2-oxo-3-[(4,5,6,7-tetrahydro-1H-indol-2-yl)methylene]-1H-indole-5-sulfonamide] (Hardyman et al, 2013). The Src inhibitor PP2 and siRNA knockdown of Src prevents rhinovirusinduced release of CXCL8 from human airway epithelial cells (Bentley et al, 2007). Analysis of an asthma protein interactome suggests that Src plays a central role and may be a good target to inhibit (Randhawa and Bagler, 2012).…”
Section: Src Family Kinase Inhibitionmentioning
confidence: 99%